2017
DOI: 10.1111/ina.12401
|View full text |Cite
|
Sign up to set email alerts
|

Pre-natal and post-natal exposure to pet ownership and lung function in children: The Seven Northeastern Cities Study

Abstract: To evaluate the association between pre-natal and post-natal exposure to pet ownership and lung function in children, a cross-sectional study named Seven Northeastern Cities (SNEC) study was conducted. In this study, children's lung function including the forced expiratory volume in 1 second (FEV ), forced vital capacity (FVC), maximal mid-expiratory flow (MMEF), and peak expiratory flow (PEF) were measured by spirometers, and pet ownership situations were collected by questionnaire. Analyzed by multiple logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…Extant literature highlights that females are disproportionately affected by impaired lung function . This is also consistent with our finding that larger negative changes in lung function measurements is associated with home renovation exposure among girls than boys.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Extant literature highlights that females are disproportionately affected by impaired lung function . This is also consistent with our finding that larger negative changes in lung function measurements is associated with home renovation exposure among girls than boys.…”
Section: Discussionsupporting
confidence: 92%
“…[23][24][25][26] Extant literature highlights that females are disproportionately affected by impaired lung function. 12,27,28 This is also consistent with our finding that larger negative changes in lung function measurements is associated with home renovation exposure among girls than boys. This may be due to the fact that females usually have smaller lung sizes and therefore have slightly greater airway reactivity than males when exposed to environmental factors, and this difference in pattern of airways response could be continued from fetal to adult life.…”
Section: Discussionsupporting
confidence: 91%
“…As for the mechanisms that increase the risk of asthma, and especially nonatopic asthma, dog ownership has been demonstrated to transport outdoor allergens indoors, promoting airway hypersensitivity and wheezing by amplifying lipopolysaccharide/toll-like receptor signals in macrophage-like cells [32]. In this analysis, we also showed that dog ownership was associated with an increased risk of a percent-predicted FEV 1 <80% at age 7, which may be related to an increased risk of asthma diagnosis in children with lower lung function [33,34]. These findings should be a step toward individual clinical advice on raising dogs in children at the highest risk of asthma.…”
Section: Discussionmentioning
confidence: 61%
“…Inverse association with any history of wheeze, mild wheeze and severe wheeze GAFFIN (2012) [74] Cat exposure at 6 months 3 years No association was found on asthma COLLIN (2015) [75] Cat/dog ownership during pregnancy (up to 28 weeks' gestation), 8 months, 2, 3, 4 and 7 years 6 months to 7 years for wheezing phenotypes 8 years for lung function Cat exposure was inversely associated with wheezing No association was found on lung function HU (2017) [76] Any pet ownership in utero, and during the first 2 years early-life exposure may have effects on respiratory health that are different from the effects exposures at other times, as it is an important window for respiratory system development. The PIAMA cohort found that early-life cat exposure was associated with reduced FVC growth in adolescence between 12 and 16 years, but there was no significant influence on MeDALL protocol-defined asthma at 17 years, while other timings of exposure during childhood had no impacts on asthma and lung function in adolescence [49,58].…”
Section: Nafstad (2001) [65]mentioning
confidence: 99%
“…The PIAMA cohort found that early-life cat exposure was associated with reduced FVC growth in adolescence between 12 and 16 years, but there was no significant influence on MeDALL protocol-defined asthma at 17 years, while other timings of exposure during childhood had no impacts on asthma and lung function in adolescence [ 49 , 58 ]. A cohort study of 7326 school-aged children in China found that pet exposure in the first 2 years of life was associated with reduced FVC [ 76 ]. Adverse associations were more likely to be reported in cross-sectional studies or nonbirth cohorts [ 76 , 77 ].…”
Section: Common Early-life Household Air Exposuresmentioning
confidence: 99%